Accentuated Eccentric Loading and Alternative Set Structures: A Narrative Review for Potential Synergies in Resistance Training - Chae, Sungwon; McDowell, Kurt W; Baur, Marten L; Long, S Alexander; Tufano, James J; Stone, Michael H (Journal of strength and conditioning research, 2024)
Chae, S, McDowell, KW, Baur, ML, Long, SA, Tufano, JJ, and Stone, MH. Accentuated eccentric loading and alternative set structures: A narrative review for potential synergies in resistance training. J Strength Cond Res 38(11): 1987-2000, 2024-As athletes become adapted to training over time, it becomes more difficult to develop their strength and power. In a conventional resistance training strategy, volume or load may be increased to provide novel stimuli to break through a plateau. However, physiological stress markers increase with increased volume or load, which is an innate shortcoming. In that case, practitioners strive to develop unconventional strategies that could increase training stimuli while adjusting fatigue. Two programming tactics, accentuated eccentric loading (AEL) using eccentric overload and alternative set structures (AS) using intraset rests, have been reported to increase training stimuli and alleviate fatigue, respectively. Importantly, when merging AEL and AS in various contexts, the 2 benefits could be accomplished together. Because AEL and AS cause different outcomes, it is important to deal with when and how they may be integrated into periodization. Moreover, prescribing eccentric overload and intraset rests requires logistical considerations that need to be addressed. This review discusses the scientific and practical aspects of AEL and AS to further optimize strength and power adaptations. This review discusses (a) scientific evidence as to which tactic is effective for a certain block, (b) potential practical applications, and (c) related discussions and future research directions.
Keywords: svalová síla; sportovci; kosterní svaly; Muscle Strength; svalová únava; Muscle Fatigue; Muscle, Skeletal; lidé; odporový trénink; Athletic Performance; sportovní výkon; Humans; Resistance Training; Athletes